2008
DOI: 10.3892/or.19.2.527
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of p-tyrosol and its derivatives may correlate with the inhibition of DNA replication initiation

Abstract: p-Tyrosol is a phenolic compound present in different dietary sources that can exert mild antioxidant properties based on in vitro and in vivo studies. In our study, two p-tyrosol derivatives (p-tyrosyl gallate and p-tyrosyl acetate) were synthesized and compared together with ptyrosol and gallic acid for their cytotoxic activities on human cancer cells. p-Tyrosyl gallate had the most potent cytotoxicity and the major cytotoxic mechanism of its action was studied. We found that in HeLa cells, p-tyrosyl gallate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Tyrosol is a naturally occurring phenol with interesting biological properties including anticancer, anti-depressant, stress-protective, cardioprotection, anti-osteoporosis, and antioxidative effects (Ahn et al 2008;Chernyshov et al 2007;Dinnella et al 2007;Panossian et al 2008Panossian et al , 2009Puel et al 2008). In our recent studies, tyrosol was derived for the first time into a novel glycoside named tyrosol galactoside (TG), and the galactoside demonstrated better anti-fatigue effect than tyrosol.…”
Section: Introductionmentioning
confidence: 96%
“…Tyrosol is a naturally occurring phenol with interesting biological properties including anticancer, anti-depressant, stress-protective, cardioprotection, anti-osteoporosis, and antioxidative effects (Ahn et al 2008;Chernyshov et al 2007;Dinnella et al 2007;Panossian et al 2008Panossian et al , 2009Puel et al 2008). In our recent studies, tyrosol was derived for the first time into a novel glycoside named tyrosol galactoside (TG), and the galactoside demonstrated better anti-fatigue effect than tyrosol.…”
Section: Introductionmentioning
confidence: 96%
“…These phenolic compounds naturally present in olives [27][28][29] may also provide added health value. p-Tyrosol, also present in wine and Rhodiola species, has been reported to have various beneficial health properties, including antioxidant and anti-inflammatory activities [28,[30][31][32]. In contrast with the numerous studies on p-tyrosol, there are only few reports regarding m-tyrosol, though it was shown to have bacteriostatic activity similar to that of HTyr and double that of ptyrosol [33].…”
Section: Discussionmentioning
confidence: 87%
“…Antioxidant activity of phenolic compounds, identified herein, can be described in terms of their intrinsic bioactivity as free radical scavengers or indirectly as modulators of intracellular pro-and antioxidant enzymes [95]. Phenolic compounds have been shown to exert antioxidant properties both in vitro and in vivo [96]. One of the phenolic compounds identified in this study was p-tert-butyl (Table 3).…”
Section: Gas Chromatography High-resolution Time-of-flight Mass Spectmentioning
confidence: 83%